AABIP evidence-informed guidelines and expert panel report for the management of indwelling pleural catheters - Miller, RJ; Chrissian, AA; Lee, YCG; Rahman, NM; Wahidi, MM; Tremblay, A; Hsia, DW; Almeida, FA; Shojaee, S; Mudambi, L; Belanger, AR; Bedi, H; et al. (Lippincott, Williams & Wilkins, 2020)
Background: While the efficacy of Indwelling pleural catheters for palliation of malignant pleural effusions is supported by relatively robust evidence, there is less clarity surrounding the postinsertion management.